Neonatal congenital microvillus atrophy. Issue 940 (17th February 2004) - Pecache, N; Patole, S; Hagan, R; Hill, D; Charles, A; Papadimitriou, J M
Abstract : Congenital microvillous atrophy (CMVA) is the leading cause of neonatal secretory diarrhoea with onset either in the first 72 hours of life (early onset) or at 6–8 weeks after birth (late onset). To date over 30 cases have been reported worldwide. The prognosis for this life threatening condition continues to be poor. Therapeutic agents like somatostatin and epidermal growth factor are either ineffective or of marginal benefit. Overall five year survival after small bowel transplantation is currently ∼50%. The following brief review is aimed towards helping neonatologists/perinatologists in the early diagnosis, and management of CMVA and in counselling the parents appropriately.